(untitled) (Revista Direito em Debate, 2022)
In this article, we aimed to interpret the Brazilian Supreme Court assumption regarding criminal prison in the second instance, based on the following milestones: Habeas Corpus (HC) 84.078-7/MG; Habeas Corpus (HC) 126.292/SP and declaratory actions of constitutionality 43, 44, and 54. For this purpose, we used the deductive method addressing doctrinal and legal discussions related to the normative and supreme force of the Constitution, penal guarantee, and the principle of presumption of innocence. Except in cases of provisional arrest, we noted that the second instance arrest violates the constitutional principle of presumption of innocence, which must last throughout the process until the final decision. Furthermore, the Supreme Court’s change of constitutional understanding motivates legal uncertainty, weakening the constitutional text. Finally, we perceived the occurrence of judicial activism when the Court gets involved in legislative power, intending to reframe the principles of res judicata and presumption of innocence.